PALEOENVIRONMENTAL AND PALEOGEOGRAPHICAL RECONSTRUCTION OF THE UPPER OLIGOCENE-MIDDLE MIOCENE NYALAU FORMATION, SOUTH BINTULU, SARAWAK, MALAYSIS - KONJING, ZAINEY (2015)
This thesis presents the result of detailed integration study of sedimentology, ichnology and palynology ofthe Upper Oligocene-Middle Miocene Nyalau Formation, south Bintulu Sarawak, East Malaysia. The studies were carried out on eleven wellexposed outcrops. Twenty facies were identified intheNyalau Formation and these are; Fl-Tabular-planar cross bedded sandstone, F2-Trough cross bedded sandstone, F3- Bidirectional cross bedded sandstone (Herringbone), F4- Flaser, wavy bedded sandstone, F5- Heterolithic sandstone, F6- Bioturbated heterolithic sandstone, F7- Ripple cross laminated sandstone, F8-Hummocky cross stratified sandstone, F9- Swaley cross stratified sandstone, F10- Parallel laminated sandstone, Fll-Interbedded hummocky cross stratified sandstone with bioturbated mudstone, F12- Laminated mudstone, F13- Heterolithic mudstone, F14- Well bioturbated mudstone, F15- Bioturbated heterolithic mudstone, F16- Carbonaceous rooted mudstone, F17- Dark fissile mudstone, F18- Coal, F19- Paleosol (Underclay) and F20- Churned, condensed bed.